Atraksi Wisata Kete’ Kesu sebagai Representasi Identitas Kelokalan Tana Toraja - Rustiyanti, Sri; Listiani, Wanda; Dwiatmini, Sriati; Ningdyah, Anrilia E. M.; Suryanti (Telkom University, 2024)
Tana Toraja is a captivating destination for tourists situated in South Sulawesi. The Tana Toraja’s traditional iconic that famous for their rich local heritage are Tongkonan and Kete’ Kesu. These architectural treasures serve as tangible expressions of Tana Toraja’s distinct cultural identity. Tongkonan and Kete’ Kesu represent non-verbal forms of folklore, categorized among the ancient legacies that include grave sites resembling boats affixed to and suspended along cave cliffs. Within these stone graves lie numerous remains of skulls and human bones, some dating back decades or even centuries, moreover, alongside these hanging stone graves. There exist grandiose tombs reserved for nobility, adorned with unique features and displaying identity photographs of the deceased. This research used a qualitative approach and ethnographic methods. The ethnographic method is one of the methods of cultural anthropology studies. This research delved into the essence of Tana Toraja’s tourist allure. Researchers directly experience the daily lives of local people, collecting data through observation and interviews. The research results mapped the elements of Tana Toraja tourist attractions in various types of folklore consisting of oral folklore, partially oral folklore, and non-oral folklore.